Tauopathy and cognitive impairment in experimental diabetes mellitus - Mariia V. Matveeva; Yulia G. SamoiIova; Natalia G. Zhukova; Oksana A. Oleynik; Maria A. Rotkank (Сахарный диабет, 2017)
Currently, diabetes mellitus (DM) is the most common metabolic disorder, which is manifested by hyperglycemia and leads to vascular and cognitive impairment. Mechanisms of cognitive dysfunction in patients with DM remain highly unclear, thus complicating the search for effective strategies for the prevention and treatment of dementia. Recently, scientists have discussed the issues regarding the relationship between DM and Alzheimer’s disease (AD), such as risk factors that trigger the cascade of pathological reactions. Patients with DM show an increased risk of developing AD. Similarly, patients with AD have been shown to have impaired insulin and glucose metabolism. Both these diseases have common nosology, pathology and biochemical basics, including oxidative stress, formation of advanced glycation end products, dysregulation of glucose metabolism and altered insulin signaling pathways. The microtubule-associated tau protein is involved in one of the causative mechanisms underlying the development of AD. We provide an overview of the major domestic and foreign data analyses regarding tau protein and the development of cognitive disorders in experimental DM.